Metabolic effects of alternate-day fasting in males with obesity with or without type 2 diabetes - Ingersen, Arthur; Helset, Hildegunn Rømma; Calov, Monika; Chabanova, Elizaveta; Harreskov, Eva Gjerlevsen; Jensen, Christina; Hansen, Christina Neigaard; Prats, Clara; Helge, Jørn Wulff; Larsen, Steen; Dela, Flemming (Frontiers in Physiology, 2022)
Alternate-day fasting induces oscillations in energy stores. We hypothesized that repeated oscillations increases insulin secretion and sensitivity, and improve metabolic health in patients with obesity with or without type 2 diabetes (T2DM). Twenty-three male patients fasted every other day for 30 h for 6 weeks. Experiments included resting energy expenditure, continuous glucose monitoring, intravenous glucose tolerance test, euglycemic hyperinsulinemic clamp, body composition, hepatic triglyceride content, muscle biopsies which were performed at baseline, during 3 weeks without allowed weight loss, and after additional 3 weeks with weight loss. Bodyweight decreased ~ 1 % and further ~3 % during weeks 1-3 and 4-6, respectively (P<0.05). Only minor changes in fat mass occurred in weeks 1-3. With weight loss, visceral fat content decreased by 13 ± 3 % and 12 ± 2 % from baseline in patients with and without T2DM, respectively (P<0.05). Hepatic triglyceride content decreased by 17 ± 9 % and 36 ± 9 % (with diabetes) and 27 ± 8 % and 40 ± 8 % (without diabetes) from baseline to week 3 and week 6, respectively (all P<0.05). Muscle lipid and glycogen content oscillated with the intervention. Glucose homeostasis, insulin secretion and sensitivity was impaired in patients with T2DM and did not change without weight loss, but improved (P<0.05) when alternate day fasting was combined with weight loss. In conclusion alternate-day fasting is feasible in patients with obesity and T2DM, and decreases visceral fat and organ-specific ectopic fat deposits. Energy store oscillations by alternate-day fasting do not improve insulin secretion or sensitivity per se.